Pengaruh Sistem Insentif dan Pelatihan Terhadap Kinerja Dimediasi Motivasi Kerja (Studi pada Konsultan Independen Oriflame Funbiz Club Surabaya) - Septiana, Hanaa’ (Jurnal Ilmiah Mahasiswa FEB, 2018)
The research is aimed to analyze the influence of incentive system and training simultaneously and partially toward performance with work motivation as the mediation on independent consultant of Oriflame Funbiz Club Surabaya. Data collection using the questionnaire as primary data and archive data from Funbiz Club Surabaya network as secondary data. The type of research used in this study is quantitative explanatory. the analysis in this research using path analysis. The researcher used 60 respondents as saturated samples. The research instruments are using normality test, validity test and reliability test, and classical assumption test which includes multicollinearity test and heteroscedasticity test. The hypothesis in this research is using F test and t-test. The result of the research is incentive system does not directly influence consultant performance, but training and work motivation simultaneously and partially toward consultant performance. In addition, incentive system and training indirectly influence toward consultant performance through work motivation on the independent consultant of Oriflame Funbiz Club Surabaya.Keywords: incentive system, training, performance, work motivation